Correction to: On inner constraints in plane circular arches - Eroglu, Ugurcan; Ruta, Giuseppe (Springer Science and Business Media LLC, 2019)
The series expansions in Eq. (16) of [1] for trigonometric functions depending on a small evolution parameter shall be corrected.